Ruins of two large temples in the Mahanaleshwar Temple Complex - Temples of India Project Team (Jio Institute, 2024)
This is a view of the north elevations of three small and two large temples in the Mahanaleshwar temple complex, most of which are in ruinous condition. Seen here are two large temples, only one of which is preserved with the shekhari variety of shikhara (superstructure). The smaller shrines have pyramidical shikharas. The exterior of the temple walls is devoid of sculptural ornamentation but with geometric patterns, diamond motifs and pillar motifs.